2007
DOI: 10.3758/bf03194129
|View full text |Cite
|
Sign up to set email alerts
|

Attentional control and reflexive orienting to gaze and arrow cues

Abstract: A wealth of data indicate that central spatially nonpredictive eyes and arrows trigger very similar reflexive spatial orienting, although the effects of eyes may be more strongly reflexive (e.g., Friesen, Ristic, & Kingstone, 2004). Pratt and Hommel (2003) recently reported that the orienting effect for arrows is sensitive to arbitrary cue-target color contingencies; for example, an attentional orienting effect for blue colored arrows is evident only for blue targets. We reasoned that if the orienting effect e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
103
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(117 citation statements)
references
References 21 publications
12
103
2
Order By: Relevance
“…In this previous report, the analysis of the latencies of error saccades was post hoc and relied on a much smaller sample than did the present experiment (n 9 vs. n 28). The interpretation that error saccades are more reflexive when elicited by gaze rather than arrow cues may therefore be premature; at least in terms of overt attentional orienting, our results challenge the suggestion that attentional orienting by gaze cues is more reflexive than orienting due to symbolic cues (Friesen et al, 2004;Ristic et al, 2007; but see Tipples, 2008). This point is most important, because it undermines the view that gaze-following is unique to biologically relevant stimuli (but see Kuhn & ticity in a strong sense is to show that spatial orienting occurs in one direction, despite participants' attempts to control volitional orienting by deploying it elsewhere (see, e.g., Driver et al, 1999).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In this previous report, the analysis of the latencies of error saccades was post hoc and relied on a much smaller sample than did the present experiment (n 9 vs. n 28). The interpretation that error saccades are more reflexive when elicited by gaze rather than arrow cues may therefore be premature; at least in terms of overt attentional orienting, our results challenge the suggestion that attentional orienting by gaze cues is more reflexive than orienting due to symbolic cues (Friesen et al, 2004;Ristic et al, 2007; but see Tipples, 2008). This point is most important, because it undermines the view that gaze-following is unique to biologically relevant stimuli (but see Kuhn & ticity in a strong sense is to show that spatial orienting occurs in one direction, despite participants' attempts to control volitional orienting by deploying it elsewhere (see, e.g., Driver et al, 1999).…”
Section: Discussioncontrasting
confidence: 55%
“…Friesen et al suggested that, as cues, eyes are more strongly reflexive than arrows, which might reflect the fact that a neural architecture is specialized for processing eyes. This finding, and its interpretation, dovetails with the results of recent behavioral (Ristic, Wright, & Kingstone, 2007) and functional neuroimaging (Hietanen, Nummenmaa, Nyman, Parkkola, & Hämäläinen, 2006;Tipper, Handy, Giesbrecht, & Kingstone, 2008) studies. However, Tipples (2008) reported involuntary orienting to counterpredictive arrow cues, thus questioning the unique status of eye gaze as a biologically distinctive directional cue.…”
mentioning
confidence: 49%
“…Previous studies that separately investigated gaze cues (e.g., Driver et al, 1999;Friesen & Kingstone, 1998) or arrow cues Tipples, 2002;Hommel et al, 2001;Eimer, 1997) found similar orienting effects, whereas studies that directly compared the two types of cue (although in separate blocks) have not provided a firm conclusion (Ristic et al, 2002(Ristic et al, , 2007Gibson & Kingstone, 2006;Friesen et al, 2004;Ricciardelli, Bricolo, Aglioti, & Chelazzi, 2002). A recent fMRI study suggested that orienting to gaze cues and arrow cues was supported by partially distinct cortical networks (Hietanen, Nummenmaa, Nyman, Parkkola, & Hämäläinen, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…Orienting after central nonpredictive cueing has been referred to as ''reflexive'' (e.g., Ristic, Wright, & Kingstone, 2007), ''involuntary'' (e.g., Gibson & Bryant, 2005), or ''deictic'' (Gibson & Kingstone, 2006). Here we adopt the term ''reflexive orienting'' because it has been widely used in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to separate earlyand late-stage motor processes, however, Cowper-Smith et al presented the central arrowheads (with 100 % validity) 700-1 Although the presentation of a central arrowhead stimulus is capable of inducing what appear to be automatic shifts of attention (Kuhn & Kingstone, 2009;Marotta et al, 2012;Ristic & Kingstone, 2006;Ristic, Wright, & Kingstone, 2007), it is clear that IOR is generated independently of any such shift of attention per se (Berger, Henik, & Rafal, 2005;Chica, Lupiáñez, & Bartolomeo, 2006;Lupiáñez et al, 2004;Martín-Arévalo, Kingstone, & Lupiáñez, 2013;Posner & Cohen, 1984). 2 If central arrowhead stimuli reveal IOR associated with a deficit in the speed of sensory or attentional processing, it should be reliably observed in studies requiring buttonpress responses to detect the onset of central arrowhead target stimuli.…”
mentioning
confidence: 99%